The Earth's magnetic field lines and earthquake relations - Ürüşan, Ahmet Yücel (Amer Inst Physics, 2 Huntington Quadrangle, Ste 1No1, Melville, Ny 11747-4501 USA, 2011)
Earthquake is one of the natural disasters and very important for human life. A lot of people die every year all over the world due to earthquakes. It is very difficult to develop early warning method for earthquakes because of it has 3000 parameters. The earthquake scientists and other people involved are very hard working about this matter. Governments allocate a significant budget for earthquakes. In this study, the earth magnetic field has been researched for early warning. The questions are any tectonic plate movement is effect of the Earth magnetic field lines or changing of the Earth magnetic field lines are effect any tectonic plate. Greater than 7 M earthquakes have been chosen in this study. And 12 years period changing graphics of the earth magnetic field lines where the chosen earthquake locals have been taken.
Keywords: Earthquake; Earth's Magnetic Field